THU0255 Methotrexate Parenteral Administration versus Oral Delivery: A Comparison of Treatment Survival Using Ontario Best Practice Research Initiative (OBRI) Cohort. (10th June 2014) - Hazlewood, G.; Jacob, B.; Akhavan, P.; Bombardier, C.
Abstract : Background: The preferred route of administering methotrexate is unclear. A recent cohort study in patients with early rheumatoid arthritis suggested improved treatment survival with subcutaneous methotrexate. Objectives: To determine the comparative drug survival and reason for discontinuation of initial treatment with parenteral methotrexate (MTX) versus oral MTX in patients with established and early rheumatoid arthritis. Methods: Patients with rheumatoid arthritis initiating methotrexate therapy were included from the Ontario Best Practice Research Initiative (OBRI), a clinical registry of early and established RA patients aged >16 years followed in routine care. In OBRI, patients are included if they had one or more swollen joints and are treated at the discretion of the rheumatologist. Patients are followed every 3 months over the first year according to a standardized protocol to collect their socio-economic characteristics, disease activities measures, medication use, mode of administration and the reason if they discontinued or switched medications. We identified patients with a new initiation of MTX at baseline or within 3 months of study entry and who were MTX-naive or minimally exposed (<12 weeks before baseline). We compared the survival between parenteral (subcutaneous and intramuscular, SC/IM)) and oral administration over the first year. Treatment failure was defined as either a change in route or discontinuation of MTX or addition/switch of any DMARDS other than glucocorticoids. Kaplan-Meir curves and log rank test were used to compare the survival between the two groups. Results: 398 patients were included (263 oral MTX, 135 sc MTX); mean (SD) age 57.3 (13.2) years, 74% female, mean symptom duration 4.4 years, mean baseline DAS28 4.9. Patients treated with parenteral MTX were more likely to receive BIOLOGICS (8.6% vs. 7.9%) and steroids (31.3% vs. 28.6%). Unadjusted Kaplan-Meier curves showed significantly improved survival with parenteral MTX (figure 1, log-rank p=0.002). The 25th percentiles of the survival time beyond which 75% of the patients in the population under study are expected not to discontinue or change MTX are 122 days (95% Confidence Interval 92-155) and 304 days (95% Confidence Interval 1214-366) for Oral and SC/IM respectively. Adverse event or side effects were reported as a significant reason for discontinuation in the parenteral group (32%) compared to oral group (15%), p<0.05. Conclusions: Parenteral MTX is associated with improved survival over oral MTX for initial treatment in patients with rheumatoid arthritis. Further analysis is required to adjust for other confounding factors. References: Hazlewood G, Thorne C, Pope J, Xiong J, Boire G, Haraoui B, Hitchon C, Keystone E, Bykerk V. Subcutaneous Delivery Of Methotrexate Is Associated With Improved Treatment Survival Compared To Oral Administration For The Initial Treatment Of Patients With Early Rheumatoid Arthritis. ACR Abstract 2013. Acknowledgements: OBRI Investigators Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5560